Examination of the role of mutualism in immune evasion - Gourmet, Lucie; Walker-Samuel, Simon; Mallick, Parag (Frontiers in Oncology, 2024)
Though the earliest stages of oncogenesis, post initiation, are not well understood, it is generally appreciated that a successful transition from a collection of dysregulated cells to an aggressive tumor requires complex ecological interactions between cancer cells and their environment. One key component of tumorigenesis is immune evasion. To investigate the interplay amongst the ecological behaviour of mutualism and immune evasion, we used a computational simulation framework. Sensitivity analyses of the growth of a virtual tumor implemented as a 2D-hexagonal lattice model suggests tumor survival depends on the interplay between growth rates, mutualism and immune evasion. In 60% of simulations, cancer clones with low growth rates, but exhibiting mutualism were able to evade the immune system and continue progressing suggesting that tumors with equivalent growth rates and no mutualism are more likely to be eliminated than tumors with mutualism. Tumors with faster growth rates showed a lower dependence upon mutualism for progression. Geostatistical analysis showed decreased spatial heterogeneity over time for polyclonal tumours with a high division rate.Overall, these results suggest that in slow growing tumors, mutualism is critical for early tumorigenesis.